PENGELOLAAN FULL DAY SCHOOL STUDI SITUS SMP ISLAM TERPADU HARAPAN BUNDA SEMARANG - Bulqis, Siti (2011)
The pupose of this study are: 1) to know the characteristics of school layout 2) to know the characteristics of students activites, and 3) to know the characteristics of learning process interactions. The object of study is Integrated Islamic Junior High School Harapan Bunda Semarang). This study is a qualitative research by ethnography design and it is limited to the head master, vice head master, teachers of class representatives, teachers, administrative staff, and the students. Data collected by observation, indepth interview, and documentation. Data analysis technique is analysis of the site.